2017
DOI: 10.3758/s13414-017-1405-7
|View full text |Cite
|
Sign up to set email alerts
|

Two kinds of bias in visual comparison illustrate the role of location and holistic/analytic processing differences

Abstract: A number of studies have shown that two stimuli appearing successively at the same spatial location are more likely to be perceived as the same, even though location is irrelevant to the task. This bias to respond "same" when stimuli are at the same location is termed spatial congruency bias. The experiments reported here demonstrate that the spatial congruency bias extends to letter strings: Participants tend to respond "same" when comparing two strings appearing successively at the same location. This bias m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…A related question is whether the physical differences in stimuli across tasks (e.g., availability of color image information, hair/background cropping, and gender variation) might have contributed to a different processing strategy and/or attentional focus across tasks. A recent paper by Cave and Chen (2017) identified an additional type of bias related to analytic versus holistic processing strategies during visual comparison tasks. They found that when stimuli could be compared as unified wholes, participants tended to use a holistic strategy, resulting in an overall greater bias to report the items as the “same,” whereas participants tended to use an analytic comparison strategy when parts of the stimuli must be compared individually, resulting in an overall bias to say “different.” Critically, this analytic/holistic bias appears to be orthogonal to the spatial congruency bias; in Cave and Chen’s study, a spatial congruency bias (difference in bias) was reported for all experiments, regardless of the direction of the overall analytic/holistic bias (Cave & Chen, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A related question is whether the physical differences in stimuli across tasks (e.g., availability of color image information, hair/background cropping, and gender variation) might have contributed to a different processing strategy and/or attentional focus across tasks. A recent paper by Cave and Chen (2017) identified an additional type of bias related to analytic versus holistic processing strategies during visual comparison tasks. They found that when stimuli could be compared as unified wholes, participants tended to use a holistic strategy, resulting in an overall greater bias to report the items as the “same,” whereas participants tended to use an analytic comparison strategy when parts of the stimuli must be compared individually, resulting in an overall bias to say “different.” Critically, this analytic/holistic bias appears to be orthogonal to the spatial congruency bias; in Cave and Chen’s study, a spatial congruency bias (difference in bias) was reported for all experiments, regardless of the direction of the overall analytic/holistic bias (Cave & Chen, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper by Cave and Chen (2017) identified an additional type of bias related to analytic versus holistic processing strategies during visual comparison tasks. They found that when stimuli could be compared as unified wholes, participants tended to use a holistic strategy, resulting in an overall greater bias to report the items as the “same,” whereas participants tended to use an analytic comparison strategy when parts of the stimuli must be compared individually, resulting in an overall bias to say “different.” Critically, this analytic/holistic bias appears to be orthogonal to the spatial congruency bias; in Cave and Chen’s study, a spatial congruency bias (difference in bias) was reported for all experiments, regardless of the direction of the overall analytic/holistic bias (Cave & Chen, 2017). In contrast, in the current study we found a complete lack of spatial congruency bias in Experiment 2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations